2014
DOI: 10.15434/kssh.2014.27.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Self-esteem in the Relationship between Body Image and Depression of Female University Students

Abstract: Purpose: The purpose of this study was to identify the mediation of self-esteem between body image and depression among female university students. Methods: This was a cross-sectional survey design. We collected 193 female university students. They was completed a self reported questionnaire including demographic characteristics, body image, self-esteem and depression. Data were collected using self-report questionnaires and analyzed with the SPSS 20.0 Program. Results: The mean age was 21.3 years old. Over 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…One Korean language study examined the relation between body image and depression. At the bivariate level, Nho et al (2014) found a negative correlation between body esteem and depression, r = −.47, p < .001. Correspondingly, the authors also found that body esteem negatively predicted depression, indicating that a more positive body image (i.e., greater esteem for one’s body) was associated with less depression.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…One Korean language study examined the relation between body image and depression. At the bivariate level, Nho et al (2014) found a negative correlation between body esteem and depression, r = −.47, p < .001. Correspondingly, the authors also found that body esteem negatively predicted depression, indicating that a more positive body image (i.e., greater esteem for one’s body) was associated with less depression.…”
Section: Resultsmentioning
confidence: 88%
“…Eight English and eight Korean language studies examined the association between body image-relevant variables (e.g., body dissatisfaction, body weight misperception) and psychosocial functioning (Choi et al, 2015; Hong, 2006b; Hwang, 2009; Jeong et al, 2013; Jung & Lee, 2006; Jung & Tae, 2004; Kim, 2014b; Kim & Aubrey, 2015; Kim & Lee, 2010; Lee et al, 2015; Lee & Lee, 2017; Lee & Yang, 2015; Lim & You, 2017; Nho et al, 2014; Oh, 2003; Sung, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many women, satisfaction with their appearance is related with satisfaction with themselves: when the appearance satisfaction is higher, they show more active attitude and higher self-esteem. When a woman has a sense of inferiority on her appearance, on the other hand, it can affect her self-concept negatively and thus cause low self-esteem (Nho JH et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the level of self-esteem is considered as an index for an individual's socio-cultural adaptation and as a motivational factor that controls one's behavior, which makes self-esteem an important concept in terms of psychosocial health (Heo NR, 2018). Female university students' body image and self-esteem have a positive correlation (Nho JH et al, 2014), and stress from appearance does affect one's self-esteem (Heo NR, 2018).…”
Section: Introductionmentioning
confidence: 99%